RANCANGAN INDEKS BERANOTASI MITOS LARANGAN PEREMPUAN HAMIL DI KECAMATAN SUTERA KABUPATEN PESISIR SELATAN - Aisyah , Yopi; Rahmi, Lailatur; Arwendria; Hasfera, Dian (UIN Imam Bonjol Padang, 2022)
This research is motivated by the absence of an information search tool regarding the myth of the prohibition of pregnant women in Sutera District. This study aims to design and produce an Annotated Index of Myths on the Prohibition of Pregnant Women in Sutera District, Pesisir Selatan Regency to facilitate users in searching for valid, effective, and practical information on myths about the prohibition of pregnant women in Sutera District. The method used in this research is the development method. The stages of the development method are needs analysis, design stage, development stage, and product testing (evaluation). The results of the effectiveness trials carried out in large groups got a value of 70% of respondents stating strongly agree and 30% of respondents agreeing and practical which was obtained in large group trials with a value of 60% of respondents stating strongly agree and 40% of respondents agreeing, this product has valid evidenced by the value of A 80%, it can be concluded that the annotated index product of the Myth of the Prohibition of Pregnant Women in Sutera District, Pesisir Selatan Regency is feasible to use.